Penentuan Mahasiswa Terbaik Dengan Menggunakan Metode Topsis (Teknik Urutan Preferensi Berdasarkan Kesamaan dengan Solusi Ideal) - Ishak, Riswandi; Suryaditya, Rachmat; Nur Khasanah, Siti; Handayani, Popon (Fakultas Teknik Universitas Hamzanwadi, 2025)
Determining the best students is a crucial process in higher education to provide recognition and motivation to outstanding students. However, manual selection processes are often subjective and time-consuming. To address this issue, this study proposes the application of the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method in identifying the best students. TOPSIS was chosen due to its ability to handle multi-criteria decision-making problems by comparing alternatives based on their proximity to the positive ideal solution and distance from the negative ideal solution. This research was conducted on Communication Science students in the Digital Communication Visual class at Bina Sarana Informatika University, utilizing evaluation criteria such as Cumulative Achievement Index (IPK), number of scientific papers, non-academic achievements, and TOEFL scores. The collected data were analyzed using the steps in the TOPSIS method, including normalization of the decision matrix, weighting, calculation of distances to the positive and negative ideal solutions, and computation of preference values for each alternative. The benefit of using TOPSIS is that it considers multiple criteria simultaneously (such as GPA, research, achievements, TOEFL, attendance, etc.), ensuring that assessments are not solely based on a single dominant factor like GPA. The results indicate that Student E achieved the highest preference value of 0.462, ranking them as the top-performing student. The application of the TOPSIS method in this study proved effective in providing objective, efficient, and transparent results in the selection process of outstanding students. Therefore, this method is recommended for implementation in the selection process of outstanding students in higher education institutions